Data Leakage Prevention and Detection System - Rajasekaran, M; Gupta, Amisha; Sharma, Padmini (International Journal of Engineering and Technology, 2018)
Our system includes a data distributor who sends some important information to some third parties, called agents in our system. Some data gets leaked and found in an unauthorized place (e.g., on the internet or somebody's PC). The distributor must be able to detect that the data got leaked and came from one or more agents. Our system detects the guilty agent, who has leaked the data to untrusted agents. For identification of leaked data in existing system uses watermarking technique. However, it has a deficiency that watermarking data can be modified or changed. So, In proposed system another technique is used for improving Â chances of detecting guilty agent is MAC (Media Access Control) address with some more prevention strategies to increase the security of the system.Â Â